TOʻQIMACHILIK SANOATI KORXONALARINING SAMARADORLIGINI BAHOLASHDA BALANSLASHGAN KOʻRSATKICHLAR TIZIMIDAN FOYDALANISH (Marketing Journal, 2026)
AbstractThis article examines the theoretical and methodological foundations forimproving efficiency in textile industry enterprises based on the Balanced Scorecard(BSC). The BSC is considered as a strategic management tool that integrates financialand non-financial aspects of enterprise activity into a unified management system. Thestudy substantiates the possibilities of performance evaluation based on the interrelation between customer relations, internal business processes, innovationdevelopment, and financial results. It is concluded that the implementation of the BSCin textile enterprises contributes to the improvement of management processes,efficient resource utilization, and enhanced competitiveness.Keywords: Balanced Scorecard, textile industry, strategic management,efficiency, financial and non-financial indicators, innovation development, internalbusiness processes, competitiveness.